Deletion of the chloroplast LTD protein impedes LHCI import and PSI–LHCI assembly in Chlamydomonas reinhardtii. (30th December 2017) - Jeong, Jooyeon; Baek, Kwangryul; Yu, Jihyeon; Kirst, Henning; Betterle, Nico; Shin, Woongghi; Bae, Sangsu; Melis, Anastasios; Jin, EonSeon
Abstract : The Chlamydomonas reinhardtii LTD null mutant generated by CRISPR–Cas9, displayed aberrant PSI–LHCI holocomplexes, suggesting that the LTD protein may selectively function in PSI–LHCI assembly in green microalgae Abstract: Nuclear-encoded light-harvesting chlorophyll- and carotenoid-binding proteins (LHCPs) are imported into the chloroplast and transported across the stroma to thylakoid membrane assembly sites by the chloroplast signal recognition particle (CpSRP) pathway. The LHCP translocation defect (LTD) protein is essential for the delivery of imported LHCPs to the CpSRP pathway in Arabidopsis . However, the function of the LTD protein in Chlamydomonas reinhardtii has not been investigated. Here, we generated a C. reinhardtii ltd ( Crltd ) knockout mutant by using CRISPR–Cas9, a new target-specific knockout technology. The Crltd1 mutant showed a low chlorophyll content per cell with an unusual increase in appressed thylakoid membranes and enlarged cytosolic vacuoles. Profiling of thylakoid membrane proteins in the Crltd1 mutant showed a more severe reduction in the levels of photosystem I (PSI) core proteins and absence of functional LHCI compared with those of photosystem II, resulting in a much smaller PSI pool size and diminished chlorophyll antenna size. The lack of CrLTD did not prevent photoautotrophic growth of the cells. These results are substantially different from those for Arabidopsis ltd null mutant, indicating LTD function in LHCP delivery and PSI assembly may not be as stringent in C. reinhardtii as it is in higher plants.